Influence of platelet and white blood cell counts on major thrombosis – analysis from a patient registry in essential thrombocythemia. (23rd May 2016) - Buxhofer‐Ausch, Veronika; Steurer, Michael; Sormann, Siegfried; Schloegl, Ernst; Schimetta, Wolfgang; Gisslinger, Bettina; Ruckser, Reinhard; Gastl, Günther; Gisslinger, Heinz
Abstract: Objectives: Although guidelines recommend normalization of platelet counts as an appropriate endpoint for treatment in high‐risk essential thrombocythemia (ET), retrospective studies could not prove a correlation of diagnostic platelet counts with an increased thrombotic rate. There is, however, an increasing evidence that leukocytosis is an important risk factor for arterial thrombosis in myeloproliferative neoplasms. Methods: This study considers the Austrian cohort of a European registry regarding the platelet‐lowering therapeutic anagrelide. Influence of platelet and white blood cell (WBC) counts on thrombotic risk was assessed. Results: Using the calculated cutoffs of 574.5 G/L for platelets and 8.48 G/L for WBC counts, respectively, the Cox regression analysis revealed a clear influence of elevated platelets ( P = 0.008) and WBC counts ( P = 0.011) on the occurrence of major thrombotic events. The time to a major thrombotic event was shortest ( P < 0.001) and the frequency related to 100 patient‐years was highest ( P = <0.001) when both platelet and WBC counts ranged above the calculated cutoffs. Conclusion: Our data add evidence to the impact of platelet and WBC counts on thrombosis in ET. We suspect a particular interaction between platelets and WBC which might be based on a biological interplay depending on particular cell counts.